Effect of Adhesive Type on the Shear Bond Strength of Metal Brackets to Two Ceramic Substrates - Mohammad Sadegh Ahmad Akhoundi; Farzaneh Aghajani; Javad Chalipa; Amir Hooman Sadrhaghighi (Tehran University of Medical Sciences, 2014)
Increased number of adult patients requesting orthodontic treatment result in bonding bracket to ceramic restorations more than before. The aim of this study was to evaluate and compare the shear bond strength of orthodontic brackets bonded to two types of ceramic bases with conventional orthodontic bonding resin and a new nano-filled composite resin.Twenty four feldespathic porcelain and 24 lithium disilicate ceramic disks were fabricated. All of the samples were conditioned by sandblasting, hydrofluoric acid and silane. Maxillary incisor metal brackets were bonded to half of the disks in each group by conventional orthodontic bonding resin and the other half bonded with a nano-filled composite. The samples then were thermocycled for 2000 cycle between 5-55° C. Shear bond strength was measured and the mode of failure was examined. Randomly selected samples were also evaluated by SEM.The lowest bond strength value was found infeldespathic ceramic bonded by nano-filled composite (p<0.05). There was not any statistically significant difference between other groups regarding bond strength. The mode of failure in the all groups except group 1 was cohesive and porcelain damages were detected.Since less damages to feldspathic porcelain was observed when the nano-filled composite was used to bond brackets, the use of nano-filled composite resins can be suggested for bonding brackets to feldspathic porcelain restorations.